Study guide to accompany : Seitz, Nelson, Harcrow, Economics of resources, agriculture, and food - Johnson, Marvin B. (McGraw-Hill, 1994)
This book is divided into five parts: Economic scope, organization, and problems os agriculture; Microeconomic concepts; Markets; Macroeconomic relationships; and Public policy and agriculture.